Genetic linkage analysis - Amos, Christopher (Henry Stewart Talks, 2004)
Likelihood formulations for genetic analysis of family data, The statistical framework for segregation and linkage analysis, Types of sampling approaches useful for linkage analysis, Modelling of linked genetic markers, The impact of linkage disequilibrium on ability to detect linkage, Modelling using less fully parametric approaches, The affected sib pair and variance components approaches
Archived at 2021/02/25